Insights into the role of Streptococcus oralis as an opportunistic pathogen in infectious diseases - Ren, Jingyi; Sun, Peng; Wang, Meijuan; Zhou, Wenjuan; Liu, Zhonghao (Frontiers in Cellular and Infection Microbiology, 2024)
Streptococcus oralis, belonging to the viridans group streptococci (VGS), has been considered a member of normal flora mainly inhabiting the oral cavity. However, more recently, there has been growing recognition of its role as a causative agent in various life-threatening infectious diseases such as infective endocarditis (IE) and meningitis. Additionally, the differences in the prevalence, clinical features, and prognosis of opportunistic infections between S. oralis and other VGS species have been addressed. Particularly the predominance of S. oralis in IE has drawn critical attention. In potentially fatal infections, clinical neglect of S. oralis as an instigating agent might significantly impede early diagnosis and treatment. Nevertheless, to date, the infectious diseases associated with S. oralis have not yet been comprehensively described. Therefore, this review will give an overview of infectious diseases caused by S. oralis to uncover its hidden role as an opportunistic pathogen.